Reprographic Activities - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
The importance of reprographics in the present context of information management system is well-recognized. Reproducing & copies from a source document through photographic, xerographic or electronic means in the least possible time is normally the service expected from a reprographic facility. http://dx.doi.org/10.14429/dbit.10.6.3024